Fabrication and characterization of a solid polymeric electrolyte of PAN-TiO2-LiClO4 - Rahman M.Y.A.; Ahmad A.; Ismail L.H.C.; Salleh M.M. (2023)
The ionic conductivity of PAN-TiO2-LiClO4 as a function of TiO2 concentration and temperature has been reported. The electrolyte samples were prepared by solution casting technique. Their conductivity was measured using the impedance spectroscopy technique. The highest room temperature conductivity of 1.8 10-4 S cm-1 was obtained at 7.5 wt % of TiO2 filler. It was observed that the relationship between temperature and conductivity were linear, fitting well in Arrhenius and not in Vogel-Tamman-Fulcher equation. The pre-exponential factor, ?0 and Ea are 1.8 10-4 S cm-1 and 0.15 eV, respectively. The conductivity data have been supported by differential scanning calorimeter (DSC) analysis. DSC analysis showed that there was a significant change in glass transition temperature (Tg) with the filler concentration. The SEM micrograph revealed that the TiO2 particles are dispersed in the electrolyte, thus enhancing its conductivity. 2009 Wiley Periodicals, Inc.